Analiza płynności finansowej GPW w Warszawie - Milo, Władysław; Wawruszczak, Maciej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Liquidity has a strong impact on the investment in the financial markets. In this paper we analyze the financial liquidity of the Warsaw Stock Exchange. By using monthly calculated measures for an individual stock, we examine the liquidity of WIG20. Our results are presented in diagrams. In conclusions, we briefly discuss the main empirical findings about the used liquidity measures and about the liquidity of The Warsaw Stock Exchange. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 27-35